1972
DOI: 10.1677/joe.0.0530349
|View full text |Cite
|
Sign up to set email alerts
|

Skin Virilism in Women With Hirsutism

Abstract: Thirteen hirsute women were studied and found to have significantly increased mean rates of sweat and sebum excretion and plasma testosterone concentration compared with control women. These same patients had previously been shown to have an increased total skin collagen content. These findings suggest that the whole skin is virilized in hirsutism. This may be the result of cutaneous androgen synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1
4

Year Published

1973
1973
1990
1990

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
3
9
1
4
Order By: Relevance
“…In the human, differences between clinically normal adult males in plasma T levels are generally moderate and coefficients of variation between 20 and 30% were reported in most studies (11,(28)(29)(30)(31)(32)(33). A diurnal variation in plasma T levels appears consistent but fairly small (34,35).…”
Section: Discussionmentioning
confidence: 93%
“…In the human, differences between clinically normal adult males in plasma T levels are generally moderate and coefficients of variation between 20 and 30% were reported in most studies (11,(28)(29)(30)(31)(32)(33). A diurnal variation in plasma T levels appears consistent but fairly small (34,35).…”
Section: Discussionmentioning
confidence: 93%
“…We have recently shown that other endocrine changes early in life also influence the way in which the adult rat responds to sebotrophic hormones (Thody & Shuster, 1971 b; Thody, Meddis & Shuster, 1977). The early endocrine environment may therefore be important in diseases such as acne and cutaneous virilism ('idiopathic hirsutes') where sebaceous activity is increased (Cunliffe & Shuster, 1969;Burton, Johnson, Libman & Shuster, 1972;Shuster, 1972). We wish to thank Mrs Lyn Carrick and Miss Linda Davison for technical and secretarial assistance.…”
Section: Discussionmentioning
confidence: 99%
“…(3) 1,178 (7) 1,966 (15) 64 (6) 4.6 (7) 3,057 (3) 87,000 (3) 85 (6) 25 (3) 486,200 (12) 1,413(6) 0(6) 2.0(7) 40.5 (7) 478 (6) 941 (8) 0 (6) 7.1 (15) 105 (15) 568 ( By using a combination of both methods (isotope infusion and direct sampling) Giusti et al (10) obtained a clear picture of androgen origin and secretion in normal women (Fig. 1).…”
Section: Adrenal Oversecretion Of Androgensmentioning
confidence: 99%
“…Starting with the concept that hair follicles as well as sebaceous glands are androgen-dependent structures (2), idiopathic hirsutism has been found to be a condition of local hyperandrogenization that involves increases in hair growth, sweat and sebum secretion, and total skin collagen content (3).…”
Section: Introductionmentioning
confidence: 99%